2006
DOI: 10.1111/j.1365-2486.2006.01210.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in aboveground primary production and carbon and nitrogen pools accompanying woody plant encroachment in a temperate savanna

Abstract: When woody plant abundance increases in grasslands and savannas, a phenomenon widely observed worldwide, there is considerable uncertainty as to whether aboveground net primary productivity (ANPP) and ecosystem carbon (C) and nitrogen (N) pools increase, decrease, or remain the same. We estimated ANPP and C and N pools in aboveground vegetation and surface soils on shallow clay and clay loam soils undergoing encroachment by Prosopis glandulosa in the Southern Great Plains of the United States. Aboveground Pros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
119
1
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 159 publications
(127 citation statements)
references
References 75 publications
6
119
1
1
Order By: Relevance
“…For soil carbon, the results are agreed with Ariapour and Asgari (2012) and Hughes et al (2006), who showed the higher C values under the trees canopies. In the literature, the enhancement of soil carbon and soil organic matter after afforestation practices is well documented fact.…”
Section: Soil Carbonsupporting
confidence: 81%
“…For soil carbon, the results are agreed with Ariapour and Asgari (2012) and Hughes et al (2006), who showed the higher C values under the trees canopies. In the literature, the enhancement of soil carbon and soil organic matter after afforestation practices is well documented fact.…”
Section: Soil Carbonsupporting
confidence: 81%
“…In the latter, woody plants may eventually suppress herbaceous plants as their density increases. These overstorey-understory relationships are influenced strongly by soil type, such that herbaceous plants may be suppressed on lowlands and facilitated on uplands (Hughes et al 2006). Local-and landscape-scale diversity perspectives should therefore be kept in mind when generalizations are made.…”
Section: Herbaceous Vegetationmentioning
confidence: 99%
“…This may be related to the expansion of woody vegetation over the past 15 years. In the Arctic tundra (Hughes et al, 2006) and lower latitudes in arid environments (Chen et al, 2014;Li et al, 2015), experimental studies provided clear evidence that climate warming is sufficient to account for the expansion of shrubs. Changes in vegetation albedo and emissivity exert feedback on climate, which is especially obvious in ET (Field et al, 2007).…”
Section: Spatiotemporal Variations In Global Terrestrial Npp and Theimentioning
confidence: 99%